Gracilaria spp. morphology cultured in brackish water pond Pantai Sederhana Village, Muara Gembong - Dinar Tri Soelistyowati; Ida Ayu Amarilia Dewi Murni; , Wiyoto (Jurnal Akuakultur Indonesia)
ABSTRACT